Corrigendum to “Revision of the NW Laurentide Ice Sheet: implications for paleoclimatic, the northeast extremity of Beringia, and Arctic Ocean sedimentation” [Quat. Sci. Rev. 28 (2009) 1573–1596] - England, John H.; Furze, Mark F.A.; Doupe, Jonathan P. (My University, 2010)
For the past half-century, reconstructions of North American ice cover during the Last Glacial Maximum have shown ice-free land distal to the Laurentide Ice Sheet, primarily on Melville and Banks islands in the western Canadian Arctic Archipelago. Both islands reputedly preserve at the surface multiple Laurentide till sheets, together with associated marine and lacustrine deposits, recording as many as three pre-Late Wisconsinan glaciations. The northwest corner of Banks Island was purportedly never glaciated and is trimmed by the oldest and most extensive glaciation (Banks Glaciation) considered to be of Matuyama age (>780 ka BP). Inside the limit of Banks Glaciation, younger till sheets are ascribed to the Thomsen Glaciation (pre-Sangamonian) and the Amundsen Glaciation (Early Wisconsinan Stade). The view that the western Canadian Arctic Archipelago remained largely ice-free during the Late Wisconsinan is reinforced by a recent report of two woolly mammoth fragments collected on Banks and Melville islands, both dated to w22 ka BP. These dates imply that these islands constitute the northeast extremity of Beringia. A fundamental revision of this model is now warranted based on widespread fieldwork across the adjacent coastlines of Banks and Melville islands, including new dating of glacial and marine landforms and sediments. On Dundas Peninsula, southern Melville Island, AMS 14C dates on ice-transported marine molluscs within the most extensive Laurentide till yield ages of 25–49 ka BP. These dates require that Late Wisconsinan ice advanced northwestward from Visount Melville Sound, excavating fauna spanning Marine Isotope Stage 3. Laurentide ice that crossed Dundas Peninsula (300 m asl) coalesced with Melville Island ice occupying Liddon Gulf. Coalescent Laurentide and Melville ice continued to advance westward through M’Clure Strait depositing granite erratics at 235 m asl that require grounded ice in M’Clure Strait, as do streamlined bedforms on the channel floor. Deglaciation is recorded by widespread meltwater channels that show both the initial separation of Laurentide and Melvile ice, and the successive retreat of Laurentide ice southward across Dundas Peninsula into Viscount Melville Sound. Sedimentation from these channels deposited deltas marking deglacial marine limit. Forty dates on shells collected from associated glaciomarine rhythmites record nearsynchronous ice retreat from M’Clure Strait and Dundas Peninsula to north-central Victoria Island w11.5 ka BP. Along the adjacent coast of Banks Island, deglacial shorelines also record the retreat of Laurentide ice both eastward through M’Clure Strait and southward into the island’s interior. The elevation and age (w11.5 ka BP) of deglacial marine limit there is fully compatible with the record of ice retreat on Melville Island. The last retreat of ice from Mercy Bay (northern Banks Island), previously assigned to northward retreat into M’Clure Strait during the Early Wisconsinan, is contradicted by geomorphic evidence for southward retreat into the island’s interior during the Late Wisconsinan. This revision of the pattern and age of ice retreat across northern Banks Island results in a significant simplification of the previous Quaternary model. Our observations support the amalgamation of multiple till sheets – previously assigned to at least three pre-Late Wisconsinan glaciations – into the Late Wisconsinan. This revision also removes their formally named marine transgressions and proglacial lakes for which evidence is lacking. Erratics were also widely observed armouring meltwater channels originating on the previously proposed never-glaciated landscape. An extensive Late Wisconsinan Laurentide Ice Sheet across the western Canadian Arctic is compatible with similar evidence for extensive Laurentide ice entering the Richardson Mountains (Yukon) farther south and with the Innuitian Ice Sheet to the north. Widespread Late Wisconsinan ice, in a region previously thought to be too arid to sustain it, has important implications for paleoclimate, ice sheet modelling, Arctic Ocean ice and sediment delivery, and clarifying the northeast limit of Beringia. Unfortunately, when this paper was originally published there were missing data in Table 2, i.e. eight Reservoir-corrected dates were not included. The correct Table 2 is printed on the following pages.
Corrigendum
Keywords: Quaternary geology; Geochronology; absolute age; Arctic Ocean; Banks Island; Beringia; C-14